Case Report: Monitoring neuromuscular fatigue through jump performance over two seasons in a cerebral palsy sprinter - Antunes, Diego; Fernandes Nascimento, Eduardo Marcel; Rossato, Mateus; da Silva, Edson Soares; de Lucas, Ricardo Dantas; Fischer, Gabriela (Frontiers in Sports and Active Living, 2025)
IntroductionWorld Para Athletics classifies athletes with brain injury, cerebral palsy, and motor coordination impairments into Group Class 31 to 38. Para athletes who can run and jump but are affected by impairments such as athetosis, ataxia, and dystonia, which impact all four limbs and the trunk, are categorized as Class T36. Monitoring training load and performance is essential for guiding training programs and preventing injuries in this population. Vertical jumps are commonly used to assess neuromuscular parameters in athletes with cerebral palsy. In this study, we tracked performance changes and monitored vertical jump height and power over two competitive seasons in a sprinter with cerebral palsy.Case presentation/methodsThe sprinter has had cerebral palsy since birth and is classified in the T36 class. Over two competitive seasons, his neuromuscular performance was monitored weekly using vertical jump tests, particularly Countermovement and Squat Jumps. His running performance was assessed through competition results. The parameters measured included Jump height and Peak power (WPEAK), which was calculated as the highest value from the curve obtained by multiplying the ground reaction force by the velocity during the concentric phase of the jump, normalized by body mass. Additionally, his official race times for the 100 m, 200 m, and 400 m events were recorded from January 2017 to October 2018.ResultsThe absolute and relative sprint performance values improved significantly between the first and the best official results: 100 m (from 15.05 s to 13.97 s = −7.1%), 200 m (from 31.30 s to 29.05 s = −7.1%); and 400 m (from 71.60 s to 66.24 s = −7.4%). The correlation between vertical jump parameters and sprint performance results was large to very large for the 100 m and 200 m events (r = 0.55–0.87).DiscussionThe Para athlete demonstrated improved performance over two seasons and didn't sustain any injuries. These findings suggest that monitoring jump performance is a valuable and practical method for tracking training loads and predicting sprint performance. Further, longitudinal studies are needed to investigate the applicability of vertical jumps as a tool for coaches to monitor training load and performance across athletes with CP from various track classifications and event types.